Strategic Management Approaches Based On Strategic Planning For Bachelor's Degree Programs In Higher Education Institutions (Basic Medical Education) - Guliyeva, Matanat; Khalilov, Taleh (Journal of Neonatal Surgery, 2025)
Higher education institutions play a crucial role in shaping the future of society, particularly in the field of medical education. The strategic management of bachelor's degree programs in medical education is essential for ensuring the quality and efficiency of academic processes, fostering innovation, and addressing the evolving needs of the healthcare sector. This study explores the significance of strategic management approaches based on strategic planning in higher education institutions, focusing on the fundamental aspects of basic medical education. The research identifies key factors that influence strategic planning in medical education, including institutional policies, accreditation standards, curriculum development, faculty development, and student engagement. Institutional policies serve as a foundation for implementing effective strategies, ensuring alignment with national and international educational standards. Additionally, accreditation and regulatory requirements play a critical role in shaping the structure and content of medical education programs. Technological advancements are another vital component of strategic management in medical education. The integration of digital learning platforms, simulation-based training, and artificial intelligence-driven teaching tools has significantly enhanced the quality and accessibility of medical education. These innovations contribute to improved learning outcomes and better preparation of future healthcare professionals. Furthermore, the study highlights the importance of continuous assessment and feedback mechanisms in strategic planning. By implementing data-driven decision-making processes, higher education institutions can adapt to changing demands and improve the overall effectiveness of medical education. In conclusion, strategic management in higher education institutions, particularly in basic medical education, requires a comprehensive approach that integrates institutional policies, technological advancements, and evidence-based strategies to ensure academic excellence and sustainable development.